North African (Algeria, Morocco and Tunisia) ammonites of the Early Jurassic (Hettangian, Sinemurian, Pliensbachian). Atlasfor species identification. - (:unkn) unknown (My University, 2017)
This atlas of ammonite identification for North Africa analyzes 241 taxa of the Early Jurassic that are replaced in their biochronological and paleogeographical contexts. It is a critical and exhaustive revision of the faunae illustrated in more than 54 paleontological studies. Furthermore a new species Parasteroceras beniderkouli sp. nov. is also described. The zone of study, about 680.000 km², covers three countries of the Maghreb (Morocco, Algeria and Tunisia). It is divided into 13 sectors corresponding to the autochthon and sub-autochthon of the northern margin of the African plate and to the North African segment of the peri-Mediterranean alpine chains. The considered period corresponds to the first three stages of the Jurassic (Hettangian, Sinemurian and Pliensbachian) and covers a little less than 20 million years. During this episode, the marine biodiversity, in particular for ammonites, knows worldwide a spectacular phase of re-diversification which furthers to the major crisis of the Trias–Jurassic boundary. In North Africa, the ammonite faunae are enough diversified and their successions enough continuous to recognize the 14 standard chronozones of the Hettangian, Sinemurian and Pliensbachian which are so going to be used as a support of the biochronological analysis. To a better understanding, a figure proposes correlations with the various zonations used in this region by some authors. The North African Domain is a part of western borders of the Tethys ocean and belongs to the southern Tethys margin. If we note a paleogeographical differentiation between the ammonite faunae of Tethyan and Euroboreal affinities that increases with time and achieves its maximum during the Pliensbachian, the presence of some NW European taxa remains rather difficult of interpretation. A possible way of transit via a “pre-Atlantic Ocean corridor”, maybe implying the Lusitanian Basin, is to be considered.
Keywords: African Research